Studies on rhizosphere microflora of pigeonpea : qualitative and quantitative incidence of microorganisms after solarization - D.S. MATHEW, ARUN ARYA and (Indian Phytopathology, 2002)
Microorganisms were isolated from non-rhizosphere and rhizosphere soils of 4 different varieties of pigeonpea after mulching. with 300 guage polyethylene sheet for 45 days. Only 6 fungi were recovered from rhizosphere of DPPA 85-5 variety while it was 9 in LRG 30. ICP 2376 and local varieties. Temperature after mulching with polyethylene sheets (150 guage) at 5 cm depth at 12.30 p.m. was increased from 42 to 46Â°C. of the four coloured sheets used. blue sheet gave the maximum temperature followed by green and black. Fusarium udum, incitant of wilt disease of pigeonpea, could not be recovered from non-rhizosphere soil after mulching for 45 days. Soil amendments with leaves of medicinal plants showed that neem leaves were most effective,